Cabbages and Kings - Henry, O., 1862-1910 (Salt Lake City, UT : Project Gutenberg, 2001)
"Cabbages and Kings" by O. Henry is a novel published in 1904 made up of interlinked short stories set in the fictitious Republic of Anchuria, a Central American country. Inspired by O. Henry's time in Honduras, the book weaves together loosely connected episodes featuring characters who appear, disappear, and occasionally return. The novel introduces the now-famous phrase "banana republic" to describe Anchuria's fruit-dependent economy and the American companies that influenced its politics. Each story ultimately connects in unexpected ways. (This is an automatically generated summary.)
The proem: by the carpenter -- "Fox-in-the-morning" -- The lotus and the bottle -- Smith -- Caught -- Cupid's exile number two -- The phonograph and the graft -- Money maze -- The admiral -- The flag paramount -- The shamrock and the palm -- The remnants of the code -- Shoes -- Ships -- Masters of arts -- Dicky -- Rouge et noir -- Two recalls -- The vitagraphoscope.
Wikipedia page about this book: https://en.wikipedia.org/wiki/Cabbages_and_Kings_(novel)
Release date is 2001-08-01
Earle C. Beach and Joseph E. Loewenstein, M.D.
Keywords: Short stories; New York (N.Y.) -- Social life and customs -- Fiction